Pediatric Asthma Among Small Racial/Ethnic Minority Groups: An Analysis of the 2006-2015 National Health Interview Survey. (July 2019) - Wen, Chi; Liu, Shelley H.; Li, Yan; Sheffield, Perry; Liu, Bian
Few studies have examined the asthma burden among small racial/ethnic minority groups such as Asian children. We examined asthma disparities among children aged 4-17 in 6 small non-Hispanic racial/ethnic minority groups (American Indian/Alaska Native [AI/AN], Asian Indian, Chinese, Filipino, other Asian, and multiple race) by using the 2006-2015 National Health Interview Survey. These small minority groups represented a weighted 6.1% of the study population (6770 of 88 049). The prevalence of current asthma ranged from 5.5% (95% confidence interval [CI], 3.5%-7.5%) among Chinese children to 13.8% (95% CI, 10.4%-17.2%) among multiple-race children and 14.6% (95% CI, 10.8%-18.4%) among AI/AN children. Compared with non-Hispanic white children, AI/AN (adjusted odds ratio [aOR] = 1.6; 95% CI, 1.2-2.2) and multiple-race (aOR = 1.4; 95% CI, 1.0-2.0) children had higher odds for current asthma. Several small racial/ethnic minority groups are at heightened risk of asthma-associated outcomes, highlighting the need for further research on these populations.